Information Technologies and Systems in The Banking Financial System - Dilfuza Erkinovna Ishankhodjaeva (Scholars Digest Publishing, 2023)
This article is devoted to the relevance of the digitalization of the country's economy, the need to change the traditional and some outdated aspects of the economy. The article is devoted to the digital development of the country's economy, with a special focus on the digitalization of the banking sector. The study presents the positive and negative consequences of this type of modernization. The purpose of the study is to assess the importance of digital transformation for the country's economy.
Keywords: digitalization, FinTech, digital economy, banking sector, technologies.